2005
DOI: 10.1037/1076-8998.10.2.155
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Versus Nonsexual Workplace Aggression and Victims' Overall Job Satisfaction: A Meta-Analysis.

Abstract: A meta-analytic approach was used to examine whether sexual and nonsexual forms of nonviolent workplace aggression (both verbal and nonverbal) share equivalent or differential relationships with victims' overall job satisfaction. When the meta-analytic comparison was restricted to all-female samples to hold victims' gender constant, nonsexual aggression was found to share a significantly stronger negative relationship with victims' overall job satisfaction than was sexual aggression. In addition, nonsexual agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
102
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(113 citation statements)
references
References 74 publications
5
102
0
3
Order By: Relevance
“…Yet, workplace aggression may have adverse outcomes that are at least as strong as those of sexual harassment. Lapierre et al (2005) found little difference in the magnitude of the relationship between these two forms of interpersonal mistreatment and job satisfaction. Further, in subanalyses of all-female samples, Lapierre et al found that victims experienced lower job satisfaction from workplace aggression than from sexual harassment.…”
Section: Comparing the Nature Of Sexual Harassment And Workplace Aggrmentioning
confidence: 89%
See 2 more Smart Citations
“…Yet, workplace aggression may have adverse outcomes that are at least as strong as those of sexual harassment. Lapierre et al (2005) found little difference in the magnitude of the relationship between these two forms of interpersonal mistreatment and job satisfaction. Further, in subanalyses of all-female samples, Lapierre et al found that victims experienced lower job satisfaction from workplace aggression than from sexual harassment.…”
Section: Comparing the Nature Of Sexual Harassment And Workplace Aggrmentioning
confidence: 89%
“…In keeping with other research (e.g., Bowling & Beehr, 2006;Lapierre et al, 2005), we combined workplace aggression measures (e.g., incivility, bullying, interpersonal conflict) into one broad aggression category and compared the outcomes of workplace aggression against the outcomes of sexual harassment. However, whereas Lapierre et al (2005) examined only global job satisfaction as the outcome variable, we examined attitudinal, behavioral, and health outcomes, and included variables that have been consistently examined in both sexual harassment and workplace aggression studies (viz. job satisfaction, coworker satisfaction, supervisor satisfaction, job stress, turnover intent, affective commitment, psychological well-being, and work withdrawal; see Bowling &Beehr, 2006, andWillness et al, 2007, for in-depth treatment of these outcomes).…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the profusion of empirical studies, discordant results have been detected, in particular when comparing studies with samples from different occupational sectors, evaluations of the perception of harassment measured with different instruments, and, especially, in studies in which samples from different continents participate. Up to the present, various quantitative reviews of this issue have been performed (Ilies, Hauserman, Schowochau & Stibal, 2003;Lapierre, Spector, & Leck, 2005;Rotundo, Ngu, & Sackett, 2001) but all of them have adopted a partial focus point or have only concentrated on one aspect of the problem, failing to base an global explanatory model on the antecedents and consequences of SH at work.…”
mentioning
confidence: 99%
“…The work of Ilies and colleagues (2003) looks at the issue from the perspective of the incidence rates of SH, detecting three main moderators-asking people whether they have experienced SH, the use of probabilistic sampling techniques, and power distances in the organizations-that could account for the great differences among the incidence rates of SH referred to in the primary studies. Lastly, the work of Lapierre et al (2005) studies the influence that SH behaviors at work can have on workers' global job satisfaction, using a procedure that compares the cases of harassment with sexual content with those that lack this connotation, but without examining other kinds of antecedents and consequences.…”
mentioning
confidence: 99%